2011
DOI: 10.1186/1479-5868-8-125
|View full text |Cite
|
Sign up to set email alerts
|

In search of causality: a systematic review of the relationship between the built environment and physical activity among adults

Abstract: BackgroundEmpirical evidence suggests that an association between the built environment and physical activity exists. This evidence is mostly derived from cross-sectional studies that do not account for other causal explanations such as neighborhood self-selection. Experimental and quasi-experimental designs can be used to isolate the effect of the built environment on physical activity, but in their absence, statistical techniques that adjust for neighborhood self-selection can be used with cross-sectional da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
554
6
21

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 698 publications
(653 citation statements)
references
References 52 publications
37
554
6
21
Order By: Relevance
“…Walkability was examined in this study because of its consistent relationship with walking in the literature and because recreational walking was the most promoted activity in the campaign. Hypothesised environmental correlates of total physical activity on the other hand have had far more mixed results [38]. Although one other study did look at a walking-specific campaign and did not find a significant moderating effect by walkability [10], only self-reported walkability was measured, without objective verification which is recommended for environmental studies on walking [39].…”
Section: Discussionmentioning
confidence: 99%
“…Walkability was examined in this study because of its consistent relationship with walking in the literature and because recreational walking was the most promoted activity in the campaign. Hypothesised environmental correlates of total physical activity on the other hand have had far more mixed results [38]. Although one other study did look at a walking-specific campaign and did not find a significant moderating effect by walkability [10], only self-reported walkability was measured, without objective verification which is recommended for environmental studies on walking [39].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these challenges and limitations, in recent years some studies that examined the effects of changes to the environment have been published [27]. One recent literature review specifically focused on causality in the relationship between the built environment and physical activity by only including quasi-experimental studies and cross-sectional studies that controlled for residential preferences [27].…”
Section: Strength Of Evidencementioning
confidence: 99%
“…Despite these challenges and limitations, in recent years some studies that examined the effects of changes to the environment have been published [27]. One recent literature review specifically focused on causality in the relationship between the built environment and physical activity by only including quasi-experimental studies and cross-sectional studies that controlled for residential preferences [27]. Surprisingly, some literature reviews a priori excluded intervention studies and focused solely on cross-sectional studies, mentioning in the discussion that environmental interventions are needed to provide causal evidence [13,[28][29][30][31].…”
Section: Strength Of Evidencementioning
confidence: 99%
“…Other studies have shown the positive effect of environmental changes on commuting behavior 12,13,14,15 . However, a large share of the evidence comes from studies in high-income countries, which may not represent the urban and sociocultural characteristics of lower-income countries like those of Latin America 3,6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence points to an association between variables in the perceived 5,9,10 and built environment 5,9,11,12 and transportation-related physical activity. Other studies have shown the positive effect of environmental changes on commuting behavior 12,13,14,15 .…”
Section: Introductionmentioning
confidence: 99%